Acute Encephalopathy with Biphasic Seizures and Late Reduced Diffusion following SARS-CoV-2 Infection—A Rare Case Report - Murthy, Manasa C.; Banerjee, Bidisha; Acharya, Ullas; Shamarao, Shivakumar (Indian Journal of Radiology and Imaging, 2023)
Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is a clinicoradiological syndrome first recognized during the influenza pandemic in Japanese population in the late twentieth century.1In this article, we presented a rare case report of AESD in a young child due to severe acute respiratory syndrome coronavirus 2 infection (SARS-CoV-2) who presented with febrile status epilepticus, persistent encephalopathy, and had recurrence of seizures on day 4 of illness with characteristic magnetic resonance imaging findings and a relatively fair outcome
Keywords: biphasic seizures; bright tree appearance; encephalopathy; febrile status epilepticus; late reduced diffusion; SARS-CoV-2 infection